Re-descriptions of eight chigger mite species (Acariformes: Trombiculidae) of the Leptotrombidium generic complex from Vietnam - Stekolnikov, Alexandr A.; Antonovskaia, Anastasia A. (Zootaxa, 2021)
Six mite species of the genus Leptotrombidium Nagayo, Miyagawa, Mitamura and Imamura, 1916 and one species from each of the genera Lorillatum Nadchatram, 1963 and Trombiculindus Radford, 1948, incompletely described by Schluger et al. (1960b, 1963) from rodents and tree shrews in North Vietnam, are re-described based on type series. Lectotypes and paralectotypes have been designated for all redescribed species. Two new synonyms have been established: Leptotrombidium magnum (Schluger, 1960) (= Leptotrombidium dooleyi Nadchatram, 1970, syn. nov.; = Leptotrombidium submagnum Wang, Li and Shi, 1988, syn. nov.).